2016
DOI: 10.1159/000452522
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Prevents Skeletal Muscle Atrophy Induced by Transforming Growth Factor Type Beta (TGF-β) via Mas Receptor Activation

Abstract: Background: Transforming growth factor type beta 1 (TGF-β1) produces skeletal muscle atrophy. Angiotensin-(1-7) (Ang-(1-7)), through the Mas receptor, prevents the skeletal muscle atrophy induced by sepsis, immobilization, or angiotensin II (Ang-II). However, the effect of Ang-(1-7) on muscle wasting induced by TGF-β1 is unknown. Aim: To evaluate whether Ang-(1-7)/Mas receptor axis could prevent the skeletal muscle atrophy induced by TGF-β1. Methods: This study assessed the atrophic effect of TGF-β1 in C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Several data, mainly from our group and others, have demonstrated the anti-atrophic effect mediated by Ang-(1-7) on skeletal muscle both in vitro and in vivo [25][26][27][28][29][30][31][32]. This is the first report that shows that Ang-(1-7) inhibits myostatin-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several data, mainly from our group and others, have demonstrated the anti-atrophic effect mediated by Ang-(1-7) on skeletal muscle both in vitro and in vivo [25][26][27][28][29][30][31][32]. This is the first report that shows that Ang-(1-7) inhibits myostatin-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 91%
“…We have also previously described that TGF-β, a growth factor of the same family as myostatin, induces muscle atrophy through an ROS-dependent mechanism [42]. Moreover, Ang-(1-7) decreases the TGF-β -dependent ROS production in myotubes [28]. Other studies must be performed in order to elucidate the source of ROS production by myostatin, and the mechanism through which Ang-(1-7) decreases ROS in response to myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that mesenchymal stem cell-conditioned media reduced muscle atrophy-related proteins in C2C12 cells 11,24,25 . To confirm whether hUCB-MSCs could prevent TGF-β1 induced muscle atrophy in C2C12 cell myotubes, we performed hUCB-MSCs coculture study in C2C12 cell myotubes treated with TGF-β1 and measured diameter in each group of C2C12 cell myotubes 24 hr after TGF-β1 treatment.…”
Section: Tgf-β1 Induced Muscle Atrophy Was Ameliorated By Hucb-mscsmentioning
confidence: 94%
“…ACE2, meanwhile, inactivates Ang II and is a negative regulator of Ang II-dependent signaling [39]. In this regard, ACE2/Ang-(1-7)/MasR in skeletal muscle shows anti-atrophic, anti-fibrotic, and anti-inflammatory activities [27,31,32,[61][62][63]. In murine models, this axis can increase the muscle strength and functionality of animals [64], and it can also increase the activity of Akt/mTOR-p70S6K, favoring the synthesis of muscle proteins.…”
Section: Ras and Its Role In The Loss Of Muscle Massmentioning
confidence: 99%